Perinatal Mental Health : a clinical guide. - Martin, Colin R. (M & K Update Ltd., 2011)
The prospect of parenthood represents a milestone in anyone's life course and is often a period of stress and challenge. There are a number of significant mental health problems that can occur during the perinatal period, the consequences of which can be both enduring and, occasionally, life threatening. However, irrespective of the specifics of the clinical manifestation of a disturbance, the distress and misery that accompanies it has significant ramifications for the mother or mother-to-be and her partner and family. This book is arranged in themed parts that represent key aspects of facili.